Optimizing Liquified Natural Gas (LNG) Transportation & Logistics - Application of Compressors and Al-Driven Analytics - Narayanan, Shankar Bhaskaran (ExcelingTech, 2025)
Liquefied Natural Gas (LNG) transportation is not just a fascinating process but also a crucial activity in the international energy market. Countries across the world are switching over from coal and crude oil to natural gas to lower carbon footprint. But natural gas has to be transported, generally over long distances, from source to place of consumption and that to in the form of liquid. Conversion of natural gas into LNG facilitates its comparatively easy and safe transport, particularly where distances are large. The entire process of transformation and transportation is very complex, but demands study due to the growing importance of LNG as an alternative fuel – a crucial element in energy transition and sustainability. This article explores the role played by compressors in the transportation of LNG. The article while adding to the pool of literature on LNG transport optimization, establishes that compressors are vital to optimizing LNG transportation and logistics. This article also establishes the utility of Artificial Intelligence (AI) in improving profitability of the players. It shows how predictive analytics be useful in enhancing the efficiency and economy of LNG transportation through the churning of huge volume of data generated at every step of the transportation process and then use it effectively to improve performance.